2002
DOI: 10.1007/s001980200016
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity and Calcium Intake with the Maintenance of Bone Mass in Premenopausal Women

Abstract: Altogether 92 initially 25- to 30-year-old women of 132 original subjects participated in this 4-year follow-up study, which evaluated the influence of physical activity and calcium intake on the bone mineral content (BMC) of premenopausal women. The subjects were originally selected for a cross-sectional study according to their level of physical activity (high PA+ and low PA-) and calcium intake (high Ca+ and low Ca-), and the original groups were maintained in this follow-up study. The mean loss of BMC (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…There are, of course, a few contrary studies that suggest lactation predicts lower BMD (261,336,352,472,559,686,770,946,971,973) or increases the risk of fracture (97,525,559,699). Smoking may cause breastfeeding to have a negative effect on BMD that is not seen in nonsmokers who breastfed (448).…”
Section: Human Datamentioning
confidence: 99%
“…There are, of course, a few contrary studies that suggest lactation predicts lower BMD (261,336,352,472,559,686,770,946,971,973) or increases the risk of fracture (97,525,559,699). Smoking may cause breastfeeding to have a negative effect on BMD that is not seen in nonsmokers who breastfed (448).…”
Section: Human Datamentioning
confidence: 99%
“…However, the findings of studies performed in young adults have not consistently produced these findings. Standard resistance-training protocols enhance muscle mass, [128][129][130][131] and in several cases bone mass, [114,132] in young women. Friedlander et al [114] reported significant increases after a 2-year programme of aerobics and weight-training in lumbar spine, intertrochanteric and calcaneal BMD.…”
Section: Young Womenmentioning
confidence: 99%
“…(15)(16)(17) The mechanisms governing the fat and lean masses and their relationships to the decrease in bone mass with age and gender are still unclear. (18) Muscular activity is well known to exert positive effects on bone mass (19,20) and hormones released by adipocytes (leptin and adiponectin)…”
Section: Introductionmentioning
confidence: 99%